Radar Absorbing Applications of Metamaterials - Varadan, V.V. (2007 IEEE Region 5 Technical Conference, 2007)
Radar absorbing materials (RAM) is used to camouflage or shield highly reflective surfaces such metallic surfaces from incident electromagnetic (EM) waves. In this paper, we explore the applications of metamaterials as conformal RAM coatings for controlling the reflection of EM waves from metal surfaces. Metamaterials are engineered materials with specially designed metallic resonant structures that are much smaller than the wavelength of incident microwaves (MW) and effectively such materials may negative permittivity and/or permeability. For the first time, we also explore the experimental use of metamaterials as conformal Frequency Selective Surfaces (FSS). Using a specially designed free space focused microwave beam automated scanning system, the reflection reduction properties of metamaterials are demonstrated for oblique angles of incidence and for orthogonal polarizations.